Human integration in an ontology-based IoT system - Skarżyński, Kamil; Bartyna, Waldemar; Stępniak, Marcin (Studia Informatica. System and information technology, 2021)
The IoT systems are growing field of automation. In contrast to industrial applications, where the system is custom made for each customer or use case, the home IoT systems can be composed and used in many, sometimes dangerous and unpredictable, ways. This paper presents a system that is based on a common ontology as a unified and universal method of representing the environment including humans. Such approach allows for easy integration of heterogenous devices and declarative definition of services, tasks, and rules ensuring human safety and/or comfort.